Media Resistance Protest, Dislike, Abstention - Syvertsen, Trine (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
‘Trine Syvertsen takes us on a historical journey through the underexplored history of how people and societies have been resisting media, from protesting and criticizing to outright rejecting them. The book is well-researched, insightful and, most of all, refreshing as it inspires readers to look and think beyond the more obvious and well-trodden paths when studying media.’ - Hilde Van den Bulck, Prof. Of Communication Studies, University of Antwerp, Belgium This book is about those who dislike, protest, and try to abstain from media, both new and old. It explains why media resistance persists and answers two questions: What is at stake for resisters and how does media resistance inspire organized action? Yet, despite the interest in media scepticism and dislike, there seems to be no book on the market discussing media resistance as a phenomenon in its own right. This book explores resistance across media, historical periods and national borders, from early mass media to current digital media. Drawing on cases and examples from the US, Britain, Scandinavia and other countries, media resistance is discussed as a diverse phenomenon encompassing political, professional, networked and individual arguments and actions.  This book is open access under a CC BY license.